Taxonomic revision of the genus Deltepilissus Pereira, 1949 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Silva, Fernando A. B.; Ferreira, Ana B. M.; Génier, François (Zootaxa, 2022)
Deltepilissus Pereira, 1949 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) is revised and consists of two valid species, both endemic to the Brazilian Atlantic Forest. Deltepilissus diabolicus (Harold, 1880), from Bahia, and D. infernalis (Harold, 1880), from Espírito Santo to São Paulo, are redescribed, including characters of the adult female and of the male genitalia, both described and illustrated here for the first time. Lectotypes are designated for D. diabolicus (Harold, 1880) and D. infernalis (Harold, 1880). A detailed literature review, synonymies, diagnoses, key for species identification, illustration of key morphological characters, as well as data of the studied material and geographic distribution are provided for each species. A discussion about their conservation status is also provided.